"I Readed the Book Last Week." The Role of Dominant Language, Receptive Vocabulary and Language Structure on Morphosyntactic Awareness in Monolingual and Heritage Language Children*. Issue 5 (3rd August 2016) - DAVIDSON, DENISE; VANEGAS, SANDRA B.; HILVERT, ELIZABETH; MISIUNAITE, IEVA
Abstract : In this research, 5- and 6-year-old monolingual (English) and heritage language (English–Spanish, English–Urdu) children completed a grammaticality judgment test to assess their awareness of grammatically correct and incorrect morphosyntactic structures in English. Results demonstrated that language group differences were minimized when heritage language children exhibited average receptive vocabulary proficiency for the sample, and when more difficult morphosyntactic structures were assessed. In this middle range, only two group differences were found. Our findings highlight the need to consider factors such as receptive vocabulary when assessing morphosyntactic awareness and language group differences.